PLAZMA TRANSFERLİ ARK KAYNAK YÜZEY İŞLEMİYLE AISI 304 PASLANMAZ ÇELİK YÜZEYİNE WC-Ni-B4C KOMPOZİT KAPLAMASININ MİKROYAPISAL KARAKTERİSTİĞİ - Buytoz, Soner; Ulutan, Mustafa; Kurt, Bülent; Islak, Serkan; Somunkıran, İlyas (e-Journal of New World Sciences Academy 2010, Volume: 5, Number: 1, Article Number: 1A0063, 2010)
Bu çalışmada, AISI 304 paslanmaz çelik yüzeyine B4C-Ni-WC karbür ve element tozlar plazma transferli ark kaynak kaplama yöntemiyle alaşımlandırılmıştır. Kaplama tabakası; optik mikroskop (OM), taramalı elektron mikroskobu (SEM), X-ışın difraktogramı (XRD) ve X ışını enerji dağılım spektrometresinden (EDS) faydalanılarak incelenmiştir. Optik mikroskop ve mikroyapı incelemeleri neticesinde, kaplama tabakası ile alt tabakanın birbirlerine metalurjik olarak bağlandığı ve yapıda ostenit (), (Cr,W)2B, Fe23(C,B)6, Cr7C3 ile Ni4B3 faz ve karbürleri belirlenmiştir. Kaplama tabakasının adhezyon aşınma direnci, yapıda mevcut karbür ve fazlardan dolayı, alt tabakaya göre oldukça yüksek değerde olduğu tespit edilmiştir. In this study, B4C-Ni-WC powder was been alloyed on the 304 stainless steel surface by using plasma transfered arc (PTA) weld surfacing process. Alloyed layer and interface were examined with optical microscope (OM), scanning electron microscope (SEM), and X-Ray diffraction (XRD) and energy dispersive spectograph. OM and SEM observations have been shown that the obtained coating had a smooth and uniform surface, as well as a metallurgical combination with the AISI 304 stainless steel substrate without cracks and pores at the interface. The austenite (), (Cr,W)2B, Fe23(C,B)6, Cr7C3 and Ni4B3 phase and carbides have been determined in the microstructure. The adhesive wear resistance of the coating layer is higher than the AISI 304 stainless steel substrate material due to the forming of hard carbides.
MICROSTRUCTURAL CHARACTERISTIC OF WC-Ni-B4C REINFORCED COMPOSITE COATINGS ON AISI 304 STAINLESS STEEL BY PLASMA TRANSFERRED ARC WELD SURFACING
Keywords: Plazma Transferli Ark Kaplama, Mikroyapı,Karbürler, Abrazif Aşınma, Bor Karbür; Plasma Transferred Arc Coating, Microstructure,Carbides, Abrasive Wear, Bor Carbide